2020
DOI: 10.3390/su13010293
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Forests: Comparing the Perceived Restorative Characteristics of Natural Soundscapes before and after the COVID-19 Pandemic

Abstract: Natural sounds are known to contribute to health and well-being. However, few studies have investigated what makes a natural sound renew and re-energize people, especially in the face of significant stressors caused by the Corona Virus Disease 2019 (COVID-19). This study examined the interactive mechanism towards the perceived restorative characteristics of natural soundscapes: fascination, being-away, compatibility, and extent. Two groups of data were collected in Burleigh Heads National Park, Australia, befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…Even the acoustic and aesthetic properties of individual sounds (bird songs and calls) are related to assessments of perceived restorativeness (Ratcliffe et al, 2020). Work by Qiu et al (2021) on natural soundscapes during the COVID-19 pandemic suggests that acoustic features of an environment can impact directly on appraisals of ART constructs of extent and fascination, while being away and compatibility may be indirect products of these appraisals. It seems timely to evaluate and update key theories of restoration in order to include acoustic properties in the same way that low-level visual features of environments are considered (see, e.g., Schertz and Berman, 2019).…”
Section: Theoretical Approaches To Sounds and Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the acoustic and aesthetic properties of individual sounds (bird songs and calls) are related to assessments of perceived restorativeness (Ratcliffe et al, 2020). Work by Qiu et al (2021) on natural soundscapes during the COVID-19 pandemic suggests that acoustic features of an environment can impact directly on appraisals of ART constructs of extent and fascination, while being away and compatibility may be indirect products of these appraisals. It seems timely to evaluate and update key theories of restoration in order to include acoustic properties in the same way that low-level visual features of environments are considered (see, e.g., Schertz and Berman, 2019).…”
Section: Theoretical Approaches To Sounds and Restorationmentioning
confidence: 99%
“…Researchers studying the restorative effects of natural sounds and soundscapes have argued for a more interpretative, constructionist approach to how individuals perceive and respond to these environments; i.e., that individuals experience natural soundscapes as a result of both bottom-up, perceptually driven processes and those that are top-down, based on existing preferences, attitudes, and cognitions (Payne, 2008;Ratcliffe et al, 2016). Compatibility between individuals and their soundscapes is also emphasized as a key predictor of perceived restoration by Qiu et al (2021).…”
Section: Associations With Nature: a New Avenue For Theoretical Development?mentioning
confidence: 99%
“…Second, natural sound is one of the factors affecting the efficacy of restorative environments [133], as the perception of natural sound aids in mental recovery [134]. In this study, we only discussed the effects of restorative environments from the perspective of vision, and did not include auditory stimuli, which may have a greater impact on healing.…”
Section: Limitationsmentioning
confidence: 99%
“…Such as, priority should be given in maximizing nature sounds over urban sounds (Browning et al, 2014). In this regard, Qiu et al, (2021) identified that during COVID-19, people with higher mental stress obtained a greater mental restoration through water sounds compared to pre-COVID samples. Based on such evidence, the presence of water such as small-scale running water both indoor and within the neighborhood should be considered as a key design principle to increase water exposure during staying at home.…”
Section: Nature Based Design (Nbd)mentioning
confidence: 96%